Aktualisasi Perempuan dalam Novel My Lecturer My Husband karya Gitlicious - Apriyani, Tristanti; Karimah, Aisyah Akhlaqul (Humanis, 2022)
Today, the development of Indonesian literature has undergone many changes, marked by the birth of female authors who present various ideas about the world of women. The world of women described by female authors does not only tell women in the domestic sphere of women but also women in the public sphere. One of them is Gitlicious in his work entitled My Lecturer My Husband. This study examines the actualization of women in the novel My Lecturer My Husband by Gitlicious by relying on the formulation proposed by Betty Friedan. This type of qualitative descriptive research uses documentation techniques and literature study as data collection methods. Meanwhile, the data analysis technique used is the interactive data analysis technique, which includes data reduction, data presentation, and data verification. The study's results prove that the actualization of women depicted in the novel My Lecturer My Husband shows the flexibility of women's roles in the public sphere. However, it does not exceed the position of men in terms of work and intelligence. Women are imaged as if they have succeeded in getting out of the domestic and public spheres so that women are aware of and reposition themselves into the domestic sphere.